Investigation of some copolymers based on acrylic salts as circulation loss control agents - Ahmed Mohamed Alsabagh; Ahmed Abd elsalam Khalil; Mahmoud Ibrahim Abdou; Hany Elsayed Ahmed; Amany Ayman Aboulrous (Egyptian Journal of Petroleum)
In this work, six copolymers were prepared from sodium and potassium acrylate. Both salts individually were copolymerized with acrylamide, methacrylic acid and acrylic acid at different ratios. The monomer reactivity ratios for copolymerization reactions of both of acrylate salts with acrylamide, methacrylic acid and acrylic acid, in solution with azobisisobutyronitrile (AIBN) as an initiator, were estimated by atomic adsorption analyser. The chemical structure was confirmed by atomic adsorption spectroscopy and FT-IR spectroscopy. The prepared copolymers were investigated as loss circulation control materials by measuring different filtration parameters such as; spurt loss, fluid loss and permeability plugging tester value according to the American Petroleum Institute (API) standard. From the obtained data, it was found that the 0.6% from the poly[PA-co-AM](0.4:0.6) exhibited the best results of the filtration parameters among the other copolymers. At the same time all the studied copolymers enhanced the rheological properties of the drilling mud. These results were discussed on the light of the swelling capacity of the copolymers.